Lipopolysaccharide significantly influences the hepatic triglyceride metabolism in growing pigs - Liu, Zhiqing (Lipids Health Dis, 2015)
BACKGROUND: In the practical commercial pig farms, inflammation is a perennial problem, yet most of studies on inflammation are focused on immune response. Actually, inflammation can induce body metabolism disorder which will finally influence animals’ growth. In this study, we investigated the effect of acute inflammation on the triglyceride (TG) metabolism in the liver of growing pigs and the possible underlying mechanisms. METHODS: Twelve male growing pigs were randomly divided into two groups, a control group (received saline) and a LPS group (intramuscular injected with 15 μg/kg LPS). Six hours after LPS injection, the pigs were euthanized and sampled. Biochemical indexes, inflammation factors, lipid metabolism related parameters and mitochondrial function were evaluated. The relationship between glucocorticoid receptor (GR) and the key enzymes of de novo lipogenesis were also investigated by chromatin immunoprecipitation assay (ChIP). RESULTS: LPS induced a serious inflammation in the liver of growing pigs proved by liver morphologic changes, the up-regulated plasma cortisol, tumor necrosis factor-α (TNF-α) content and gene expression of inflammation related genes in liver. For de novo lipogenesis, LPS significantly decreased the gene expression of fatty acid synthase (FAS), Acetyl-CoA carboxylase-1 (ACC-1) and Stearoyl-CoA desaturase-1 (SCD-1), and the protein expression of ACC-1 and SCD-1. For lipolysis, only the gene expression of adipose triglyceride lipase (ATGL) was decreased. LPS did nothing to the gene expression of hormone-sensitive lipase (HSL) and the lipolytic enzymes activities. For β-oxidation, LPS significantly increased the protein expression of CPT-1α, but the gene expression of mitochondrial DNA-encoded genes and the activities of mitochondrial complex IV and V demonstrated no obviously changes. Furthermore, ChIP results showed that LPS significantly decreased the level of GR binding to ACC-1 promoter. CONCLUSION: LPS infection has a profound impact on hepatic TG metabolism. This impact is mainly demonstrated by the significantly deceased de novo lipogenesis, and GR may involve in its regulation.